2005
DOI: 10.1016/s0002-9440(10)62235-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Consumption Accelerates Fibrosis in Response to Cerulein-Induced Pancreatitis in Rats

Abstract: Alcohol consumption is a risk factor for chronic pancreatitis (CP), but the mechanism in humans remains obscure because prolonged alcohol consumption in most humans and animal models fails to produce alcoholic chronic pancreatitis (ACP). We hypothesize that the process leading to ACP is triggered by a sentinel acute pancreatitis (AP) event; this event causes recruitment of inflammatory cells, which initiates fibrosis driven by the anti-inflammatory response to recurrent AP and/or chronic oxidative stress. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 58 publications
7
100
1
1
Order By: Relevance
“…Because of this, the inflammatory response in chronic alcoholic pancreatitis has also been investigated [80] . Using rats pair-fed the Lieber-Decarli diet, Deng et al [80] demonstrated that chronic ethanol administration reduced the number of resident mononuclear cells in the pancreas.…”
Section: Role Of the Inflammatory Response In Alcoholic Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this, the inflammatory response in chronic alcoholic pancreatitis has also been investigated [80] . Using rats pair-fed the Lieber-Decarli diet, Deng et al [80] demonstrated that chronic ethanol administration reduced the number of resident mononuclear cells in the pancreas.…”
Section: Role Of the Inflammatory Response In Alcoholic Pancreatitismentioning
confidence: 99%
“…Because of this, the inflammatory response in chronic alcoholic pancreatitis has also been investigated [80] . Using rats pair-fed the Lieber-Decarli diet, Deng et al [80] demonstrated that chronic ethanol administration reduced the number of resident mononuclear cells in the pancreas. They, like others, suggested that this reduction likely reflects a general immunologic suppression in the pancreas of animals chronically fed ethanol [17,78] .…”
Section: Role Of the Inflammatory Response In Alcoholic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol abuse may not be the sole risk for the development of CP [32] ; rather alcoholic CP is likely the result of an interaction of several co-factors [2] . It has been demonstrated that chronic alcohol consumption accelerates fibrosis in response to cerulein-induced CP in rats [33] . Alcohol metabolites in pancreatic acinar cells induce persistent cytosolic Ca 2+ signals in a concentration-dependent manner and depolarize mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the macrophages are found in proximity to areas of fibrosis (16,98). Lipopolysaccharide (LPS)-activated macrophages stimulate pancreatic stellate cell (PSC) activation and promote collagen and fibronectin synthesis in cultured PSCs (77).…”
Section: Monocytes/macrophagesmentioning
confidence: 99%